Between rock and a hard place : The impact of home country demand on exclusive international strategic alliances forged by new technology ventures - Sardana, Deepak; Gupta, Narain; Khan, Huda (Elsevier, 2025)
This study seeks to progress the relatively thin body of scholarly research on the exclusive characteristics of strategic international alliances forged globally, particularly by new technology ventures. Due to the liability of smallness and newness, these new ventures need to strategically adopt exclusivity in licensing to secure partners across the globe to help them overcome the lack of resources and market access capability. Adopting resource dependence theory, the present study suggests that market size is a key consideration for the determinants of exclusive licensing for new technology ventures. The study investigates if the home demand of a country will influence the propensity to form exclusive international partnerships for new technology ventures. Based on the dataset of 545 international partnerships across the globe, findings of the study provide strong support to the idea that new ventures based in developed countries with limited market size (i.e., small-developed countries) are disproportionately more inclined to offer exclusive partnerships. Significant and positive moderation to the above findings were found due to the effect of sub-sectors, but not due to the size of the partner firms in the international market. The post-hoc analysis considering international and domestic alliances combined sample indicated consistent findings. The findings have theoretical, practical, and policy related implications for international strategic partnerships.
Keywords: Exclusive partnerships; International strategic alliances; New ventures; High technology; Resource dependence theory; Home country demand